Sensitivity of prick test with walnut commercial extracts and of prick by prick with raw walnut compared with open food challenge in walnut allergy: Low SPT sensitivity in walnut allergy - Patti, Maria Letizia; De Rose, Cristina; Brancato, Federica; Gambacorta, Alessandro; Miceli Sopo, Stefano (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Diagnosis of walnut allergy includes the evaluation of IgE sensitization by skin prick tests (SPT) with standardized commercial extracts. When assuming the loss of relevant allergens due to extract preparation and storage, it is possible to perform SPT with fresh foods, i.e., prick by prick (PbP). To our knowledge, there is no published comparison between SPT with commercial extracts and PbP with fresh food about their sensitivity to the diagnosis of walnut allergy. Therefore, we describe our experience. Methods: We observed seven children (mean age + SD 6.8 years + 5.2, range 2 - 15 years; male 85%) with an history of immediate adverse reaction following walnut ingestion. All but one the patients underwent SPT with at least two out of three walnut commercial extracts (Lofarma, Milan, Italy; ALK-Abellò, Milan, Italy; Allergopharma, Rome, Italy). It has also been performed PbP with raw walnut. IgE-mediated walnut allergy was diagnosed based on suggestive history, positivity of PbP and failed open food challenge with walnut. Results: The SPT with Lofarma extract was never positive (sensitivity = 0%), that performed with ALK extract was positive in 2/5 cases (sensitivity 40%) and that of Allergopharma extract was positive in 1/5 cases (sensitivity 20%). PbP was positive in 7/7 cases (sensitivity 100%). Conclusions: In the specific case of walnut allergy in pediatric age, the execution of SPT alone with commercial extract may not be sufficient and clarifying in the diagnostic iter. We suggest to always associate the execution of PbP test.